FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDE AS DETERMINANTS OF FINANCIAL SATISFACTION: THE MEDIATING ROLE OF FINANCIAL BEHAVIOR IN WELMA MYBCA - Yulli; Ihsan, Mohammad; Solikhin, Agus (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study examines the role of financial knowledge on financial behavior, financial attitude on financial behavior, financial knowledge on financial satisfaction, financial attitude on financial satisfaction, financial attitude on financial satisfaction, financial behavior on financial satisfaction, and to determine the role of financial behavior in the influence between financial knowledge on financial satisfaction, the mediating role of financial behavior in influencing between financial attitude on financial satisfaction of Welma myBCA application users at PT Bank Central Asia, Tbk. Although the number of BCA customers who have investment products is still relatively small compared to the total customer base, the fastest growth comes from the young customer segment. This growth was driven by the integration of Welma into the myBCA application, simplification of the investment process, easy access to investor identity, and adjustments to transaction limits and nominals that increase the attractiveness and accessibility of investment products for the younger generation. A mixed-methods approach was adopted, combining quantitative analysis using SEM-Partial Least Squares with 384 respondents who used Welma in the myBCA application. The findings showed that financial knowledge and financial attitude have a positive and significant effect on financial behavior and financial satisfaction in customers who use the Welma myBCA application. In addition, financial behavior has a positive effect on financial satisfaction and acts as a mediating variable that strengthens the influence of financial knowledge and financial attitude on financial satisfaction. These findings confirm that increased financial knowledge and good financial attitudes encourage healthy financial behavior, which ultimately increases customer financial satisfaction.